Simplified distribution grid model for power quality studies in the presence of photovoltaic generators. Issue 6 (1st August 2015) - Patsalides, Minas; Efthymiou, Venizelos; Stavrou, Andreas; Georghiou, George Elia
Abstract : Renewable energy sources are expected to have a considerable share in the global energy mix over the next years and consequently further research is required to enhance the planning strategies, modify prudently the existing standards and set quality levels on delivered power in order to accommodate the penetration of these technologies. Depending on the distribution grid dynamics and the load demand, the amplitude of voltage may vary significantly, and therefore proper simulation models are required for performing dedicated studies. In this study, a simplified and accurate model representing the distribution grid dynamics is introduced for power quality studies in the presence of distributed photovoltaic (PV) generators. The proposed simplified distribution grid model (SDGM) is validated using measurements and it is then used along with a verified PV system model to estimate the voltage variation and PV capacity of the distribution grid under investigation. Moreover, a sensitivity analysis is performed by varying the parameters of the SDGM to assess how the PV capacity is altered. As a last step, common voltage regulation schemes are analysed through the use of the proposed model, validating operational modes that can accommodate high distributed PV capacities.